Juridical Analysis of Hospital Liability for Nosocomial Infections - C.Yudhistira; D.Saragih (The Medical Journal of Hospital Management and Health Law, 2026)
Introduction: Healthcare-associated infections, traditionally known as nosocomial infections, present a critical intersection between medical practice and legal accountability. Patients who acquire infections during hospital stays face prolonged recovery, increased financial burdens, or even mortality, raising profound questions regarding the legal responsibilities of healthcare providers. Methods: This study employs a normative juridical research method, analyzing primary legal sources, statutory regulations, and relevant judicial precedents to evaluate hospital liability frameworks. Results: The findings indicate that hospital liability for nosocomial infections shifts between contractual default and tortious negligence, heavily dependent on the institutional failure to enforce statutory Patient Safety Standards and strict sanitation protocols. Discussion: The discussion delves into the intricate balance between the medical standard of care and the legal definition of negligence. It reviews extensive literature concerning the doctrine of res ipsa loquitur and corporate liability, demonstrating that hospitals cannot easily evade liability if systemic failures in infection control are proven, even when specific medical staff behavior is not overtly negligent. Conclusions: This study concludes that while absolute liability is unfeasible due to inherent medical risks, a robust framework of corporate fault must be enforced, requiring proactive compliance with healthcare regulations. It is recommended that regulatory bodies tighten supervision and hospitals implement comprehensive, legally verifiable clinical risk management systems to mitigate both medical and legal exposures.